Gender stereotypes fixing in lexicographical works - Чуєшкова, Оксана Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article is devoted to the consideration of gender stereotyping in modern explanatory vocabulary works. The most common gender stereotypes are classified, recommendations on avoiding this phenomenon are expressed. The importance of creating non-discriminatory language is emphasized, the role of dictionaries in this process depending of their informative and regulatory functions is underlined.